COPE: Community Outreach & Professional Engagement – a framework to bridge public mental health services with religious organizations - Milstein, Glen; Currier, Joseph M.; Dent, Charles; McKnight, Melissa; Eckert, David; Manierre, Amy (Frontiers in Psychiatry, 2025)
The primary purpose of public mental health is to promote wellbeing. The World Health Organization (WHO) and the Substance Abuse and Mental Health Services Administration (SAMHSA) have found that it is crucial to engage community to improve wellbeing and to support persons at times of stress. The United States Surgeon General has reported on significant debilitation caused by an epidemic of loneliness, contributed to by the loss of social connections through fewer and less vibrant social infrastructures. WHO, SAMHSA and the Surgeon General recognize that spiritual/faith-based organizations (SFBOs) are prevalent social infrastructures, dispersed geographically, as well as found across diverse economic, ethnic, immigrant, well-served and underserved communities. Because of their prevalence and social connectedness, what role could SFBOs play to improve social cohesion and individual wellbeing, increase community support, reduce dysfunction and sustain recovery? How could mental health service organizations (MHSOs) engage SFBOs in collaborative care? This paper will review evidence that supports the role of religion and spirituality (R/S) to both promote wellbeing, as well as to respond to stressors in ways that can both prevent the onset of mental disorders and support recovery after clinical treatment. We also review negative attributes of R/S that can be the source of trauma and also impede access to mental health care. We provide a framework for Community Outreach & Professional Engagement (COPE) to guide collaborations that originate in MHSOs and reach out to SFBOs to build relationships that can become partnerships. Key principles of COPE are to recognize that community and clinic are separate domains, that clergy have both religious and cultural expertise pertinent to wellbeing and social support, and that clinicians have expertise pertinent to assessment and treatment for dysfunction. COPE is a framework to bridge these separate domains in order to facilitate community-engaged collaborative care, which is clinically crucial for persons with more severe mental illness or substance abuse to sustain their recovery. We provide case examples of the COPE categories of collaboration, and include recommendations for future research in the context of outcomes for public mental health.